Sensitive and Rapid Detection of the Plasmid-Encoded Colistin-Resistance Gene mcr-1 in Enterobacteriaceae Isolates by Loop-Mediated Isothermal Amplification - Zou, Dayang; Huang, Simo; Lei, Hong; Yang, Zhan; Su, Yuxin; He, Xiaoming; Zhao, Qinghe; Wang, Yong; Liu, Wei; Huang, Liuyu (Frontiers in Microbiology, 2017)
The emergence of the plasmid-encoded colistin-resistance gene mcr-1 in Enterobacteriaceae represents a new threat to the treatment of infection in the clinical setting. A sensitive and rapid molecular method for detection of the mcr-1 gene in clinical isolates is needed to control the spread of this gene. In this study, we established a loop-mediated isothermal amplification (LAMP) assay for rapid detection of the mcr-1 gene. This assay was applied to cultured bacteria and spiked human stools. Real-time monitoring of turbidity and chromogenic visualization were used to assess the reaction results. The specificity and sensitivity of the primers in the LAMP reactions for detection of the mcr-1 gene were determined. All 20 clinically resistant isolates without the mcr-1 gene tested negative, indicating the high specificity of the LAMP primers. The sensitivity of LAMP, with a detection limit of 0.2 pg/μL DNA, was 10-fold greater than that of polymerase chain reaction (PCR). The assay was also conclusive when applied to human stools spiked with mcr-1-positive Escherichia coli. During clinical screening in a major hospital in Beijing, China, seven isolates were identified as positive from the 556 Enterobacteriaceae isolates. In conclusion, the LAMP assay we developed was useful for detection of the mcr-1 gene in the clinical setting.